2018
DOI: 10.1177/1467358417751026
|View full text |Cite
|
Sign up to set email alerts
|

Sea turtles tourism in Oman: Current status and future prospects

Abstract: This paper provides an overview of the current status and future potentials of nature-based tourism in the Sultanate of Oman with particular focus on sea turtles at Ras Al Hadd. The paper uses objective yardsticks such as inbound tourist arrivals, nationality and spending patterns, seasonality, employment, as well as gross domestic product contribution derived from secondary data from national and international sources to appraise the current situation. Additionally, based on the review of relevant literature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…their topics and research findings) revealed the following six main themes: state religion and tourism (Zamani-Farahani and Henderson, 2010); food security and tourism (Pirani and Arafat, 2016); tourism and growth (Saleh et al, 2015); tourism and immigrants (Balli et al, 2018, 2019); tourism and the environment (Gladstone et al, 2013); and finally tourism planning and development (e.g. Busaidi et al, 2019; Ebrahim and Ganguli, 2017; Michael et al, 2019; Sharpley, 2008). The last of these themes is the most dominant research topic, accounting for 65.21% of the total research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…their topics and research findings) revealed the following six main themes: state religion and tourism (Zamani-Farahani and Henderson, 2010); food security and tourism (Pirani and Arafat, 2016); tourism and growth (Saleh et al, 2015); tourism and immigrants (Balli et al, 2018, 2019); tourism and the environment (Gladstone et al, 2013); and finally tourism planning and development (e.g. Busaidi et al, 2019; Ebrahim and Ganguli, 2017; Michael et al, 2019; Sharpley, 2008). The last of these themes is the most dominant research topic, accounting for 65.21% of the total research.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the tourism sector is growing as the second section shows, it faces several barriers to destination development. Depending on the country, these include (i) dependence on foreign labor, (ii) insufficient enforcement of existing regulations, (iii) weak tourism infrastructure and facilities in some countries, (iv) strong competition between GCC countries to provide an almost identical tourism product, (v) the risk of political unrest, (vi) social and cultural norms that may contradict the expectations of Western tourists, and (vii) a lack of effective coordination and partnership among service providers and public–private partnerships (Busaidi et al, 2019; Henderson, 2006, 2015; Mansfeld and Winckler, 2007, 2008; Sharpley, 2002). On the other hand, the GCC countries are endowed with factors that can facilitate destination development, such as (i) a developed infrastructure for water sports activities and a well-preserved marine and desert ecotourism setting, (ii) a stable and safe environment, (iii) a welcoming local population that creates a positive perception among travelers, (iv) modern infrastructure and communications, (v) developed shopping facilities and amenities (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oman is presently succeeding with the governmental strategies in addition to plans to turn its economy from oil-based to a tourism-based economy (Faghih & Zali, 2018;Al Busaidi et al, 2018). Oman has been a member of World Trade Organization (WTO) since 2000.…”
Section: Oman Economic Strategymentioning
confidence: 99%
“…Several large-scale infrastructure projects in the GCC are planned, in line with the future economic visions of many GCC countries. 1 The implementation of these long term economic plans promises a secure future for the development of Takaful industry (Elkaftangui and Mohamed 2019;Busaidi et al 2019;Alshuwaikhat et al 2016;Diab 2015;Goodman et al 2015;Alobaidi et al 2015;Al-Maadid et al 2018).…”
Section: Introductionmentioning
confidence: 99%